Augmented reality, virtual reality, and computer graphics : 6th International Conference, AVR 2019, Santa Maria al Bagno, Italy, June 24-27, 2019, Proceedings.: 6th International Conference, AVR 2019, Santa Maria al Bagno, Italy, June 24-27, 2019, Proceedings. Part I (2019) - Unknown
No abstract available